BREAST CANCER SURVIVORS HAVE LESS LEAN MASS AND LOWER PHASE ANGLE AFTER CANCER TREATMENT - Verde, Sara Maria Moreira Lima; Justa, Rute Mattos Dourado Esteves; Machado, Vitória Maria Queiroz; Lima, Carone Alves; Castro, Ádila da Silva; Araújo, Camilla Oliveira Duarte (Mastology, 2019)
Objective: To evaluate the weight status and body composition of women who survived breast cancer after cancer treatment. Methods: This is a before and after clinical study, in which 27 breast cancer survivors were evaluated before (T0) and after (T1) cancer treatment (surgical and clinical). Current weight and height were measured to determine the body mass index (BMI). Body composition was assessed by tetrapolar bioelectrical impedance. The percentage of fat and lean mass and the phase angle were calculated. We used Student’s t-test to assess the difference among means of anthropometric variables and body composition between T0 and T1, and the McNemar’s test to evaluate differences in the prevalence of overweight, adopting a 5% significance. Results: Patients have a mean increase of 2.6 kg in weight after treatment (p=0.00) and 1.15 km/m2 in BMI (p=0.00). The percentage of fat mass increased by 0.6% (p=0.003) in T1, while the lean mass decreased (p=0.03). Concerning the phase angle, the mean decrease is 0.6 (p=0.026) after treatment. Conclusion: Breast cancer survivors have increased adiposity, decreased lean mass, and compromised cell integrity after cancer treatment, suggesting elevated risk factors for disease recurrence.